2021
DOI: 10.1159/000518508
|View full text |Cite
|
Sign up to set email alerts
|

Serial Monitoring and Hyperimmunoglobulin versus Standard of Care to Prevent Congenital Cytomegalovirus Infection: A Phase III Randomized Trial

Abstract: <b><i>Introduction:</i></b> Nonrandomized studies support the potential of cytomegalovirus hyperimmunoglobulin (CMV-HyperIg) in preventing maternofetal CMV transmission, but prospective interventional studies show equivocal results. We pre­sent a prospective phase-III international randomized open-label trial on the potential effect of CMV-HyperIg following serial monitoring of CMV serostatus. <b><i>Methods:</i></b> CMV-seronegative pregnant women (gestational ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Another alternative is the administration of CMV hyperimmune globulins to infected pregnant women during their first trimester of pregnancy. Although some recent randomized controlled trials investigating the efficacy of hyperimmune globulins did not find a significant reduction in the incidence of cCMV infection [116,155,156], an observational study with the administration of hyperimmune globulins twice a month showed promising results in decreasing mother-to-child transmission rate [157]. However, the fact remains that hyperimmune globulin therapy during pregnancy is much more expensive than valaciclovir, and it may cause severe allergic reactions in rare cases (1/203 in the study by Hughes et al [111]).…”
Section: To Reduce the Risk Of Maternal-fetal Transmission In Case Of...mentioning
confidence: 99%
“…Another alternative is the administration of CMV hyperimmune globulins to infected pregnant women during their first trimester of pregnancy. Although some recent randomized controlled trials investigating the efficacy of hyperimmune globulins did not find a significant reduction in the incidence of cCMV infection [116,155,156], an observational study with the administration of hyperimmune globulins twice a month showed promising results in decreasing mother-to-child transmission rate [157]. However, the fact remains that hyperimmune globulin therapy during pregnancy is much more expensive than valaciclovir, and it may cause severe allergic reactions in rare cases (1/203 in the study by Hughes et al [111]).…”
Section: To Reduce the Risk Of Maternal-fetal Transmission In Case Of...mentioning
confidence: 99%
“…Cahill et al 35 and Albright et al 36 each carried out a cost-effectiveness analysis of maternal CMV screening but their conclusions are not applicable to the French healthcare system because they included treatment with hyperimmunoglobulin to reduce vertical transmission of CMV, but this is not readily available in France and does not seem to be efficient in significantly reducing vertical transmission 37,38 . In our model, the antenatal costs and effectiveness (number of infected fetuses and children diagnosed) were concordant with those of the recent French study published by Seror et al 34 , who focused on the costs and effectiveness of screening for T1 CMV PI during pregnancy, in conjunction with valacyclovir treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no evidence-based treatment options to prevent fetal CMV infection following CMV seroconversion during pregnancy [ 12 ]. Many questions remain unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…The virus is transmitted, for example, through infectious urine (diaper changes) or saliva (shared cutlery) of the infected child [ 11 ]. Unfortunately, basic prevention methods, such as vaccines, have not been shown to be effective [ 12 14 ]. Treatment options for CMV during pregnancy are limited and controversial (cytomegalovirus immunoglobulin or antiviral drugs) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation